Experiences of higher level students in the context of the pandemic: the transition from classroom to remote teaching - Álvarez Hernández, Gabriel Alejandro (2021)
This article is a report of an investigation carried out with students of the degrees in Pedagogy and Educational Psychology of the National Pedagogical University Unit 096 in Mexico City in the framework of the pandemic caused by the SARS-CoV-2 virus (COVID- 19). This pandemic caused the transfer of face-to-face courses to distance courses, so that the students who collaborated in this research had the experience of this change of modality in an emergent way and without a previous didactic strategy. This had didactic consequences, since the teaching staff did not have the pedagogical training to work remotely and the student community was neither trained nor had the experience. To carry out this research, the qualitative approach, hermeneutical phenomenology as an epistemological basis and the narrative biographical method were used. For their part, the instruments were questionnaires through Google forms and interviews by meet, which were applied to 80% of the student population in the period from March to July 2020. The results obtained revealed that each teacher elaborated their own strategy to complete the courses, while the student body experienced multiple forms derived from what each teacher proposed to them. The foregoing, among other factors, generated an environment of uncertainty and confusion that altered the course of their studies. It concludes with the need to develop pedagogical strategies that allow a collegiate and approved work, so that the learning objectives are achieved.